Tradisi Bongkar Lubuk Larangan Di Muara Sipongi : Perspektif Hukum Islam - Aminudin Aminudin; M. Iqbal Irham (Mahesa Research Center, 2024)
This research explains the activity of unloading lubuk ban, namely a tradition of harvesting fish in the Batang Girls River which was previously prohibited for a year by customary rules. This tradition has been going on for decades in the Mandailing Natal community. This research is qualitative and was carried out by collecting, analyzing, and providing a comprehensive interpretation so as to produce perfect data about the tradition of dismantling the lubuk ban. The results of this research conclude that the tradition of dismantling the lubuk ban in Simpang Mandepo Village, Muara Sipongi District, not only prioritizes the principles of benefit and maslahat (goodness), but also uses environmentally friendly tools, thus bringing in a lot of good fortune for the community.